Ucapan Terima Kasih Tim Editor JAL Vo. 4, No. 2, Oktober 2018 - JAL, Pengelola (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018, 2018)
Ucapan Terima Kasih Tim Editor JAL Vo. 4, No. 2, Oktober 2018